Youth on screen representing young people in film and television - Buckingham, David 1954- (Cambridge, United Kingdom Polity Press, 2021)
Right from the origins of cinema, countless films and television dramas have offered sensational and seductive representations of young people's lives. Youth is typically associated with energy, idealism and physical beauty, but it is often represented as both troubled and troubling. These representations are almost always created by adults, implicitly reflecting an adult perspective on how young people 'come of age.'

Youth on screen provides a historical account of representations of youth in Britain and the United States stretching back over seventy years. From Blackboard Jungle to This is England, and from Jailhouse Rock to Skins, it covers a range of classics, as well as some intriguing obscurities. Engagingly written and clearly organized, it offers a perfect introduction for students and general readers.
Introduction -- Troubling teenagers : how movies constructed the juvenile delinquent -- Dreamboats, boybands and the perils of showbiz : the rise and fall of the pop film -- Reeling in the years : retrospect and nostalgia in movies about youth -- Gender trouble : cinema and the mystery of adolescent girlhood -- This is England : growing up in thatcher's Britain -- Skins and the impossibility of youth television -- Conclusion : histories and futures.
Includes bibliographical references and index.
Keywords: Youth in motion pictures; Youth on television